Enhancing the combustion properties of interface optimized metastable intermixed composites PVDF/μ-Al by noncovalently functionalized graphene. (November 2022) - Deng, Haoyuan; Yi, Zhuoran; Shen, Qiang; Qin, Mei; Sun, Yi; Luo, Guoqiang
Graphical abstract: Highlights: The SPEEK modified grapheme (SPG) prepared by non-covalent modification of sulfonated polyether-ether-ketone was introduced into PVDF/Al to improve its energy release. The optimized interface generated by the interaction between SO3 H groups of SPG layer and CF2 dipoles of PVDF layer integrates graphene onto the surface of PVDF/Al particles. Abstract: Energetic metastable intermixed composites (MICs) consisting of polyvinylidene fluoride (PVDF) and fuels aluminum (Al) have the potential to be used as propellants and explosives. Our study introduced SPEEK-modified graphene (SPG) prepared by non-covalent modification of sulfonated poly(ether-ether-ketone) (SPEEK) into PVDF/Al to improve its energy release. The optimized interface generated by the interaction between SO3 H groups of SPG layer and CF2 dipoles of PVDF layer integrates graphene onto the surface of PVDF/Al particles. Due to the effect of graphene on the interfacial thermal resistance, the enthalpy of SPG coated PVDF/Al particles is about 1.5 times higher than that of uncoated particles. The existence of SPG improves the heat transfer efficiency of MICs. For comparison, reduced graphene oxide (RGO) has also been introduced as an additive. Graphene is introduced to linearly affect(R 2 = 0.9865) the main oxidation enthalpy by lifting the surface oxidation heat release of the Al core. Therefore, graphene is a new strategy for increasing the energy release rate while improving the energy output.